International Material-Product Chains: An Alternative Perspective on International Trade and Trade Theories - Pieter J.H. van Beukering; Jeroen C.J.M. van den Bergh; Marco A. Janssen; Harmen Verbruggen (Tinbergen Institute, 2000)
The relationship between trade and material flows is examined by viewing theglobal economy from the perspective of international material-product chains(MPC). The international MPC covers the complete lifecycle of a material or aproduct in two or more regions, including extraction, production, consumption,waste management and transport. Products, waste, and associated material flowsin the international MPC can run vertically or horizontally between segments.It is demonstrated how differences in factor requirements across segments ofthe international MPC in combination with factor productivity differencesacross developed and developing countries can cause specific trade patterns ofinter-industry and intra-industry flows of materials and products. Theimplications of considering various trade theories in the context of the ideaof an international MPC are examined. This interpretation of internationaltrade sheds a new light especially on the physical dimension of internationalspecialisation.
Keywords: 330; Materialfluss; Stoffstrommanagement; Lebenszyklus; Außenwirtschaftstheorie; Umweltpolitik; Kreislaufwirtschaft; Welt